Weld consumables and PWHT for P92 power plant steel - Chalk, Kieran (2013)
P92 steel is a high-alloy steel that has been specifically designed for operating at high temperatures (600°C - 650°C) and has found wide use in the power generation industry, particularly since 2005. For the successful installation and use of this advanced steel, all aspects of its behaviour, in terms of both metallurgy and in-service behaviour, must be investigated. Investigating all the relevant material aspects is beyond the scope of a single PhD, and so the Supergen consortium funds a number of projects working on different material aspects. The purpose of this thesis is to investigate, and seek a greater understanding of, the behaviour of welds in P92 steel so that their in-service behaviour may be better understood particularly the response of the material to post-weld heat treatments (PWHT), the optimum weld consumable composition and the microstructural development during creep-rupture. This understanding has been achieved through a combination of microstructural characterization, thermodynamic modelling and mechanical testing.